Reply to Roggero and Minolli's Commentary: Restoring the Working Alliance, or Crisis and Developmental Opportunity? Mismatching and Reparation in Multiple Different Meanings. Issue 5 (2nd September 2016) - Cavelzani, Alessandro; Tronick, Ed
Abstract : The commentary by Maria Pia Roggero and Michele Minolli offers interesting points that enrich and clarify the discussion: the application of theoretical tenets to clinical practice and research, and different viewpoints on the concept of mismatching. We argue that miscommunication, misunderstanding, and loss of coordination cause mismatching exchanges and rupture the emotional connection between caregiver and infant as well as between analyst and patient (Tronick, 2007). We think that the process of mismatching and reparation is actually a developmental opportunity to dyadically expand the consciousness of infant and patient, as well as parent and therapist (Minolli, 2015).